2003
DOI: 10.1007/s00464-002-8826-6
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic management of complications following laparoscopic Roux-en-Y gastric bypass for morbid obesity

Abstract: A variety of complications can present after LRYGB. Laparoscopy is an excellent technique to treat these complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
69
2
6

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(85 citation statements)
references
References 23 publications
8
69
2
6
Order By: Relevance
“…The large decrease in mesenteric fat after distal gastrectomy is a major cause of weight loss after surgery [17,18]. As a result, a large weight loss may increase the size of the mesenteric defect, thus accelerating the internal hernia [19].…”
Section: Resultsmentioning
confidence: 99%
“…The large decrease in mesenteric fat after distal gastrectomy is a major cause of weight loss after surgery [17,18]. As a result, a large weight loss may increase the size of the mesenteric defect, thus accelerating the internal hernia [19].…”
Section: Resultsmentioning
confidence: 99%
“…Two of the procedures involve a stapled anastomosis with either circular or linear staplers, potentially reducing technical complexity and the duration of the procedure. The reported rates for complications after stapled gastrojejunostomy are 1.1 to 6% for leaks, 2.9 to 27.1% for strictures, and 1.6% for intraluminal bleeding [16][17][18][19][20][21][22][23]. The third accepted technique is the hand-sewn gastrojejunostomy originally promoted by Higa et al [24].…”
Section: Discussionmentioning
confidence: 99%
“…Internal herniation is the most common cause for bowel obstruction after LRYGBP in most series (Table 2). [6][7][8][9][10][11][12][13][14] Higa et al 13 reported that internal herniation occurred in 63 of 2000 patients (3.1%) who underwent LRYGBP. Champion et al 7 reported internal herniation in 6 of 13 bowel obstructions in their series of 711 laparoscopic gastric bypasses.…”
Section: Discussionmentioning
confidence: 99%
“…Others have reported late obstruction at this site as a result of scarring at the transverse mesocolon defect. 7,11 Gould et al 6 reported an obstruction of the Roux limb, which had twisted in the retrocolic tunnel. A twisted Roux limb can result in obstruction and possibly ischemic bowel, resulting in a leak.…”
Section: Discussionmentioning
confidence: 99%